Problematika Persamaan Hak Dalam Waris dan RAD - Ahsin, Mohammad; Khosyiah, Siah; Mukhlas, Oyo Sunaryo (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2024)
Islamic inheritance law is a provision for the transfer of property from a deceased person to the person left behind. Islamic inheritance law in Indonesia has been regulated in KHI in accordance with Presidential Instruction Number 1 of 1991. The purpose of this study aims to determine the position and fair rights attached to both male and female heirs in receiving inheritance, especially in cases of kalalah and radd. The method used in this research is normative juridical, namely by conducting searches of library materials, laws and other literature. Kalalah is a person who dies without leaving a father and children. Debate arises regarding the determination of the meaning of walad which is a requirement for siblings to obtain inheritance. KHI in article 182 seems to globalize the word walad. KHI takes the opinion of Ibn Abbas ra. that the word walad includes boys and girls in order to create gender justice. The radd is the excess of inheritance after being distributed to the heirs and there are no 'asabah heirs. In this radd issue, KHI follows the opinion of Uthman bin Affan that the excess is returned to all heirs as stated in article 193.